Comparison of serum biochemical markers in patients with mesothelioma and pleural plaques versus healthy individuals exposed to environmental asbestos - Döngel, İsa; Akbaş, Ali; Benli, İsmail; Bayram, Mehmet (Baycinar Medical Publishing, 2019)
Background: In this study, we aimed to compare serum biochemical markers in patients with malignant pleural mesothelioma and pleural plaques versus healthy individuals exposed to environmental asbestos. Methods: Between September 01, 2010 and March 31, 2011, a total of 540 participants (354 males, 186 females; mean age 61.4 years; range, 35 to 89 years) were included in the study. The participants were divided into four groups as follows: (1) patients with pleural plaques (n=277); (2) healthy individuals with normal chest X-rays who were exposed to environmental asbestos (n=121); (3) healthy individuals with normal chest X-rays who were not exposed to environmental asbestos (n=118); and (4) patients with malignant pleural mesothelioma (n=24). Serum levels of carcinoembryonic antigen, cancer antigen 125, 15-3, 19-9, free T3, free T4, thyroidstimulating hormone, vitamin B12, folate, and ferritin were measured. Results: Serum cancer antigen 125, 15-3, folic acid, vitamin B12, and ferritin levels were higher with lower free T3 levels in Group 4 than the other groups. The areas under the curve for cancer antigen 125 and 15-3 were 0.78 and 0.67, respectively in the differential diagnosis of mesothelioma from other pathologies (p < 0.001 for both). Optimal limits of these biomarkers were 13.63 and 18.43 ng/mL, respectively with 83% and 75% sensitivity and 69% and 48% specificity, respectively. Conclusion: The combination or individual use of serum cancer antigen 125, 15-3, folic acid, vitamin B12, and ferritin levels may be helpful for early diagnosis and treatment of malignant pleural mesothelioma.

Amaç: Bu çalışmada mezotelyoma ve plevral plaklı hastaların çevresel asbest maruziyeti yaşamış sağlıklı bireylere kıyasla serum biyokimyasal belirteçleri karşılaştırıldı. Çalışma planı: 01 Eylül 2010 - 31 Mart 2011 tarihleri arasında toplam 540 katılımcı (354 erkek, 186 kadın; ort. yaş 61.4 yıl; dağılım, 35-89 yıl) çalışmaya alındı. Katılımcılar dört gruba ayrıldı: (1) plevral plaklı hastalar (n=277); (2) çevresel asbeste maruz kalıp göğüs röntgenleri normal olan sağlıklı bireyler (n=121); (3) çevresel asbeste maruz kalmadan göğüs röntgenleri normal olan sağlıklı bireyler (n=118) ve (4) malign plevral mezotelyomalı hastalar (n=24). Serumda karsinoembriyonik antijen, kanser antijeni 125, 15-3, 19-9, serbest T3, serbest T4, tiroid stimülan hormon, B12 vitamini, folik asit ve ferritin düzeyleri ölçüldü. Bulgular: Diğer gruplara kıyasla, Grup 4’te serum kanser antijeni 125, 15-3, folik asit, B12 vitamini ve ferritin düzeyleri daha yüksek ve serbest T3 düzeyleri daha düşük idi. Mezotelyomanın diğer patolojilerden ayırıcı tanısında kanser antijeni 125 ve 15-3’ün eğri altında kalan alanı sırasıyla 0.78 ve 0.67 idi (her ikisi için de p<0.001). Bu biyobelirteçlerin optimum sınırı sırasıyla 13.63 ve 18.43 ng/mL olup, duyarlılıkları sırasıyla %83 ve %75 ve özgüllükleri %69 ve %48 idi. Sonuç: Serum kanser antijeni 125, 15-3, folik asit, B12 vitamini ve ferritin düzeylerinin birlikte veya tek başına kullanımı, malign plevral mezotelyomanın erken tanı ve tedavisinde yararlı olabilir.
Mezotelyoma ve plevral plaklı hastaların çevresel asbest maruziyeti yaşamış sağlıklı bireylere kıyasla serum biyokimyasal belirteçlerin karşılaştırılması
Keywords: Biochemical Marker; Ferritin; Mesothelioma; Pleural Plaque; Biyokimyasal Belirteç; Ferritin; Mezotelyoma; Plevral Plak